2006
DOI: 10.1590/s0100-84042006000400015
|View full text |Cite
|
Sign up to set email alerts
|

Reações de defesas químicas e estruturais de Lonchocarpus muehlbergianus Hassl. (Fabaceae) à ação do galhador Euphalerus ostreoides Crawf. (Hemiptera: Psyllidae)

Abstract: -(Structural and chemical defensive reactions of Lonchocarpus muehlbergianus Hassl. (Fabaceae) to Euphalerus ostreoides Crawf. (Hemiptera: Psyllidae) galling stimuli). Galls are plant structure induced in response to stimuli of a gall-inducing organism. Euphalerus ostreoides induces galls on the adaxial surface of leaflets directly on secondary veins of Lonchocarpus muehlbergianus. Anatomical analyses were performed to compare healthy leaflets, immature and mature gall tissues. Histochemical tests for detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
0
34
0
3
Order By: Relevance
“…In fact, some authors have demonstrated the induction of a nutritive reserve in galls induced by sap-feeders (e.g., Meyer 1987, Oliveira et al 2006, Moura et al 2008. Herein, we measured tissue developmental changes between non-galled leaves and galls throughout ontogeny to establish possible convergences between gall systems involving gallinducers with similar mouth apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some authors have demonstrated the induction of a nutritive reserve in galls induced by sap-feeders (e.g., Meyer 1987, Oliveira et al 2006, Moura et al 2008. Herein, we measured tissue developmental changes between non-galled leaves and galls throughout ontogeny to establish possible convergences between gall systems involving gallinducers with similar mouth apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos envolvendo a anatomia e a ontogênese de galhas (Arduin & Kraus 1995, Kraus et al 1996, Kane et al 1997, Souza et al 2000, Kraus et al 2002, Kraus et al 2003, Oliveira et al 2006 confirmam que os padrões de alteração da morfogênese são complexos e evidenciam uma interação espécie-específica.…”
Section: Introductionunclassified
“…Estas alterações são acompanhadas por modificações bioquímicas, principalmente notadas em relação a metabólitos primários e secundários específicos. Alterações estruturais e químicas têm grande influência na manutenção do ciclo de vida dos galhadores, o qual se passa parcial ou totalmente dentro dos tecidos vegetais, sendo o galhador responsável pela formação, desenvolvimento e manutenção das galhas (Oliveira et al, 2006). Abrahamson & McCrea (1986) sugeriram que o fenótipo da galha é um resultado da interação entre dois genótipos.…”
Section: Introductionunclassified